China's global identity : considering the responsibilities of great power - Hoo, Tiang Boon, 1977- (Georgetown University Press, 2018)
What kind of great power will China become? It is uncertain how or if China's growing power, interests, and ambitions can be successfully accommodated within the current American dominated international order. Tiang Boon Hoo has undertaken the most in-depth examination to date of how Chinese elites view China's future role in the world. Without being blind to the potential dangers of China's rise, Hoo's findings force a reexamination of assumptions that China aims to be a revisionist power. In fact, even before Bill Clinton famously called for China to become a responsible great power in 1995, Chinese leaders were already considering this very issue. Hoo has conducted extensive field research in China and has analyzed several decades' worth of Chinese policy papers, speeches, and the work of Chinese scholars to better understand how the Chinese perceive their role as a rising great power. While China's best intentions do not ensure a peaceful rise, this book will help outside observers understand China's self-perceptions and intentions and to reconsider assumptions about the inevitability of US-China conflict.